CURRENT STATE AND FEATURES OF AGRIBUSINESS DEVELOPMENT IN UZBEKISTAN (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The agribusiness sector in Uzbekistan has been experiencing significant transformation and development in recent years. This change is driven by the government's efforts to modernize agriculture, attract foreign investment, and improve food security. Key features of agribusiness development in Uzbekistan include the diversification of crops, introduction of advanced technologies, and enhancement of supply chain management. This article explores the current state of agribusiness in Uzbekistan, highlighting its features, challenges, and opportunities for further advancement.